Relationship between BMI and prognosis of chronic heart failure outpatients in Vietnam: a single-center study - Nguyen, Hoai Thi Thu; Ha, Thuong Thi Thu; Tran, Hieu Ba; Nguyen, Dung Viet; Pham, Hung Manh; Tran, Phuong Minh; Pham, Tuan Minh; Allison, Thomas G.; Reid, Christopher M.; Kirkpatrick, James N. (Frontiers in Nutrition, 2023)
Background: Insufficient data exists regarding the relationship between body mass index (BMI) and the prognosis of chronic heart failure (CHF) specifically within low- and middle-income Asian countries. The objective of this study was to evaluate the impact of BMI on adverse outcomes of ambulatory patients with CHF in Vietnam. Methods: Between 2018 and 2020, we prospectively enrolled consecutive outpatients with clinically stable CHF in an observational cohort, single-center study. The participants were stratified according to Asian-specific BMI thresholds. The relationships between BMI and adverse outcomes (all-cause death and all-cause hospitalization) were analyzed by Kaplan-Meier survival curves and Cox proportional-hazards model. Results: Among 320 participants (age 63.5 ± 13.3 years, 57.9% male), the median BMI was 21.4 kg/m 2 (IQR 19.5-23.6), and 10.9% were underweight (BMI <18.50 kg/m2). Over a median follow-up time of 32 months, the cumulative incidence of all-cause mortality and hospitalization were 5.6% and 19.1%, respectively. After multivariable adjustment, underweight patients had a significantly higher risk of all-cause mortality than patients with normal BMI (adjusted hazard ratios=3.03 [95% CI: 1.07-8.55]). Lower BMI remained significantly associated with a worse prognosis when analyzed as a continuous variable (adjusted hazard ratios=1.27 [95% CI: 1.03-1.55] per 1 kg/m 2 decrease for all-cause mortality). However, BMI was not found to be significantly associated with the risk of all-cause hospitalization (p>0.05). Conclusions: In ambulatory patients with CHF in Vietnam, lower BMI, especially underweight status (BMI<18.5 kg/m 2 ), was associated with a higher risk of all-cause mortality. These findings suggest that BMI should be considered for use in risk classification, and underweight patients should be managed by a team consisting of cardiologists, nutritionists, and geriatricians.